Hadirat Tuhan dalam Ruang Digital: Kajian Teologis terhadap Ibadah Online di tengah Pandemi Covid-19 - Daniel Kristanto Gunawan (STFT Jakarta, Indonesia, 2022)
The pandemic period forced the church to change its way of service from onsite to online, including Sunday service. The church tries to bring an atmosphere of worship in person in the church moving to the house or any other place through virtual worship in the digital space. However, it turns out that attendance at online church services is a problem. Some think the presence in the digital space is less real than the presence in the analog room. How can attendance at online worship be validated as a natural body presence in the liturgy? Will the people experience an encounter with God’s presence through worship in the digital space? This paper attempts to examine the experience of being present through the point of view of practical theology. I reconstruct the meaning of presence in worship in the digital space by emphasizing a model of fellowship in the Triune God.